Pengaruh Kompetensi, Independensi, Objektivitas dan Sensitivitas Etika Profesi Terhadap Kualitas Hasil Audit (Studi Pada BPKP Jawa Timur) - Alvionita, Eka; Malikah, Anik; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study aims to analyze the influence of competence, independence, objectivity, and professional ethics sensitivity on audit quality at BPKP East Java. Using a quantitative approach, data were collected through questionnaires distributed to auditors at BPKP East Java from August to September 2021. The results indicate that competence and professional ethics sensitivity significantly impact audit quality, while independence and objectivity do not show significant effects. These findings highlight the importance of enhancing auditors' competence and ethical sensitivity to ensure higher audit quality. The study also suggests that future researchers consider other factors such as auditor knowledge and stress levels, and expand the sample size to enrich the findings.Keywords: Competence, independence, objectivity, professional ethics sensitivity, audit quality.